My Secret Unicorn : Friends forever - Chapman, Linda (London : Puffin, 2006)
Lauren can't wait to go to pony camp with her best friend, Mel. It's going to be so much fun sharing a cabin, riding ponies and having picnics. But when she gets there everything goes wrong....
Keywords: Friendship -- Fiction; Ponies -- Fiction